Kemampuan Daya Ledak Otot Tungkai dan Kecepatan Pemain Bola Voli Klub Sehase Lubuklinggau - Remora, Hengky; Suhdy, Muhammad (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to describe how the level of leg muscle explosive power and speed of Sehase Lubuklinggau club volleyball. This research is a type of quantitative descriptive research with one variable without making comparisons or connecting with other variables. In this study, the population numbered 20 people and became a sample of 20 players who actively participated in training activities at the Sehase Lubuklinggau using the total sampling technique. The instruments used in this study were the Vertical Jump Test to measure the explosive power of the leg muscles and the 30-meter run test to measure speed. The results of this study indicate that: 1) The explosive power ability of the leg muscles of the volleyball players of the Sehase Lubuklinggau club in 2023 obtained an average of 115.18 in the Good category. 2) The speed ability of the Sehase Lubuklinggau club volleyball btained an average of 4.28 in the Good category. Keywords: Volleyball, Explosive Power, Speed, Leg Muscles.